Respuesta :

Answer:

[tex]f(x)=-\sqrt{2x^3-2x+4}[/tex]

Step-by-step explanation:

Given:

[tex]\frac{dy}{dx}=\frac{3x^2-1}{y}[/tex]; [tex]y=-2[/tex] when [tex]x=1[/tex]

Separate the differentials:

[tex]y\frac{dy}{dx}=3x^2-1[/tex]

[tex]ydy=(3x^2-1)dx[/tex]

Integrate both sides:

[tex]\int\limits {y} \, dy=\int\limits {3x^2-1} \, dx[/tex]

[tex]\frac{1}{2}y^2=x^3-x+C[/tex]

Solve for the constant C:

[tex]\frac{1}{2}(-2)^2=(1)^3-(1)+C[/tex]

[tex]2=C[/tex]

Plug in C and solve for y:

[tex]\frac{1}{2}y^2=x^3-x+2[/tex]

[tex]y^2=2x^3-2x+4[/tex]

[tex]y=-\sqrt{2x^3-2x+4}[/tex] (since [tex]y=-2[/tex], the radical has to be negative)

Substitute y=f(x):

[tex]f(x)=-\sqrt{2x^3-2x+4}[/tex]

Ver imagen goddessboi